Optical film, polarizer protective film, polarizing plate, and image display device
By adopting a three-layer optical film, using a (meth)acrylic resin composition with a ring structure in the main chain, the problems of optical film adhesion and hard particle shedding are solved, and high slipibility and resistance are achieved Threshing properties improve manufacturing efficiency.
Patent Information
- Application Number
- CN202380049400.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-11
AI Technical Summary
During the winding of the optical film, the adhesion problem of the optical film leads to a reduced manufacturing efficiency, and the shedding of hard particles may lead to surface defects and contamination.
An optical film with a three-layer structure, wherein the first outermost layer and the second outermost layer are formed of a resin composition containing hard particles, and the intermediate layer is formed of a (meth)acrylic resin composition having a ring structure on the backbone, Ensure that the glass transition temperature relationship of the resin composition meets specific conditions to improve slipibility and threshing resistance.
The optical film is achieved with high slipibility and threshing resistance, which improves manufacturing efficiency and reduces the risk of surface defects and contamination.
Smart Images

Figure BDA0005205416500000041 
Figure BDA0005205416500000051 
Figure BDA0005205416500000052
Abstract
Description
Technical Field
[0001] The present disclosure relates to an optical film, a polarizing plate protective film, a polarizing plate, and an image display device. Background Art
[0002] (Meth)acrylic resins have excellent optical properties and are used as materials for optical films constituting liquid crystal displays, for example.
[0003] As optical films, optical films with single-layer structures and optical films with multi-layer structures are known in the past. As an example of an optical film with a multi-layer structure, there is a thermoplastic resin film, which is a thermoplastic resin film composed of at least three layers A / B / A of A layer and B layer, wherein the A layer is formed of an amorphous thermoplastic resin A with a glass transition temperature of 80 to 120°C, and the B layer is formed of an amorphous thermoplastic resin B with a higher glass transition temperature than the resin A, and the thermoplastic resin film has a light transmittance of 90% or more, a haze value of 1.0% or less, and a film thickness of 20 to 200 μm (Patent Document 1).
[0004] The optical film is produced, for example, by a melt film forming method. A typical melt film forming method includes: a step of melting a resin composition as a material of the optical film; a step of molding the molten resin composition into a film shape; and a step of winding the solidified optical film into a roll.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-125688 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In the process of winding the optical film into a roll, the adhesion of the optical film often becomes a problem. "Adhesion" means that the films are closely attached to each other and difficult to peel off. If the adhesion of the optical film is suppressed, the manufacturing efficiency of the optical film is improved. In order to suppress adhesion, it is required to ensure the slipperiness of the surface of the optical film.
[0010] In order to ensure the slipperiness of the optical film, hard particles called anti-adhesive agents are used in the material of the optical film. The hard particles are present on the surface of the optical film, thereby preventing the films from being closely attached to each other and ensuring the slipperiness of the surface of the optical film. However, the hard particles protrude from the surface of the optical film and thus sometimes fall off from the optical film. If a large number of hard particles fall off from the surface of the optical film, for example, it is possible that defects on the surface of the optical film become apparent, and it is possible to contaminate the rollers of the manufacturing device constituting the optical film.
[0011] An object of the present disclosure is to improve the slipperiness of the surface of an optical film and the grain-shedding resistance of the surface of the optical film.
[0012] Technical Solution
[0013] The present disclosure provides the following optical film described in [1], the polarizing plate protective film described in [2], the polarizing plate described in [3], and the image display device described in [4].
[0014] [1] An optical film comprising: a first outermost layer formed from a first resin composition; a second outermost layer formed from a second resin composition; and an intermediate layer disposed between the first outermost layer and the second outermost layer, the intermediate layer being formed from a (meth)acrylic resin composition comprising a (meth)acrylic resin having a ring structure in the main chain, the first resin composition and the second resin composition comprising hard particles, the glass transition temperature Tga of the first resin composition, the glass transition temperature Tgb of the second resin composition, and the glass transition temperature Tgc of the (meth)acrylic resin composition satisfying the following formula (A) and the following formula (B).
[0015] Formula (A): Tga>Tgc.
[0016] Formula (B): Tgb>Tgc.
[0017] [2] A polarizing plate protective film comprising the optical film described in [1].
[0018] [3] A polarizing plate comprising the polarizing plate protective film according to [2].
[0019] [4] An image display device comprising the polarizing plate described in [3].
[0020] Effects of the Invention
[0021] According to the present disclosure, an optical film having excellent lubricity can be provided. In addition, according to the present disclosure, the threshing resistance of the optical film can be improved. DETAILED DESCRIPTION
[0022] The embodiments of the present disclosure are described. Of course, the present disclosure is not limited to the following embodiments. In the following description, "(meth)acrylic acid" is used as a term including both "methacrylic acid" and "acrylic acid". Resin and polymer are used as terms with the same meaning. Resin composition is used as a term to represent a composition that contains at least one resin and may contain other resins, additives, etc. When a numerical range is expressed as X to Y, it means greater than X and less than Y. For example, "50% to 99%" means greater than 50% and less than 99%.
[0023] [Optical film]
[0024] An optical film of one embodiment of the present disclosure comprises: a first outermost layer formed from a first resin composition; a second outermost layer formed from a second resin composition; and an intermediate layer disposed between the first outermost layer and the second outermost layer and formed from a (meth)acrylic resin composition comprising a (meth)acrylic resin having a ring structure in the main chain.
[0025] The first outermost layer, the second outermost layer, and the intermediate layer are stacked as one. The "integrated" mentioned here means that the optical film is not separated naturally due to its own weight, etc., and is not easily separated by manual operation of the operator. For example, a solution of temporarily stacking multiple layers by adhesion with separation as a prerequisite is not included in this embodiment.
[0026] The first resin composition and the second resin composition contain hard particles. The hard particles are so-called anti-blocking particles.
[0027] The glass transition temperature Tga (unit: °C) of the first resin composition, the glass transition temperature Tgb (unit: °C) of the second resin composition, and the glass transition temperature Tgc (unit: °C) of the (meth)acrylic resin composition satisfy the following formula (A) and the following formula (B).
[0028] Formula (A): Tga>Tgc.
[0029] Formula (B): Tgb>Tgc.
[0030] The glass transition temperatures of the first resin composition, the second resin composition, and the (meth)acrylic resin composition can satisfy the above formula (A) and formula (B) as long as they are determined by the same measurement method. The glass transition temperature of the resin composition constituting each layer can be determined by separating each layer and measuring it by differential scanning calorimetry (DSC).
[0031] Preferably, the first outermost layer, the second outermost layer and the intermediate layer are stretched.
[0032] The thickness of the optical film may be, for example, 1 to 200 μm, and from the viewpoint of further improving the mechanical properties of the optical film, preferably 5 to 100 μm, and more preferably 10 to 60 μm.
[0033] The ratio of the sum of the thickness of the first outermost layer and the thickness of the second outermost layer to the thickness of the intermediate layer may be, for example, 0.1:99 to 50:50. From the viewpoint of making the amount of particles in the first outermost layer and the second outermost layer appropriate and better achieving both lubricity and transparency, the ratio is preferably 0.5:99.5 to 47.5:52.5, and more preferably 2.5:97.5 to 45:55.
[0034] The haze value of the optical film is preferably 1.4% or less, more preferably 1.0% or less, and further preferably 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less.
[0035] In this embodiment, the intermediate layer is in contact with the first outermost layer and the second outermost layer. The optical film may further include other layers between the first outermost layer and the intermediate layer, and between the second outermost layer and the intermediate layer, unless the characteristics of the optical film of this embodiment are impaired.
[0036] (Middle layer)
[0037] The intermediate layer is formed of a (meth)acrylic resin composition. The (meth)acrylic resin composition includes a (meth)acrylic resin having a ring structure in the main chain. The (meth)acrylic resin having a ring structure in the main chain includes a structural unit derived from a (meth)acrylic ester monomer (hereinafter referred to as a (meth)acrylic ester unit) and a structural unit including a ring structure formed in the main chain (hereinafter referred to as a ring structural unit).
[0038] The (meth)acrylate unit may be, for example, a structural unit derived from the following monomers: methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, o-tolyl (meth)acrylate, phenoxyethyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, glycidyl (meth)acrylate, and the like. The (meth)acrylic resin may contain only one type of (meth)acrylic acid ester unit, or may contain two or more types of (meth)acrylic acid ester units.
[0039] Specifically, the ring structural unit may be a glutaric anhydride structural unit, a glutarimide structural unit, a maleic anhydride structural unit, an N-substituted maleimide structural unit, a lactone ring structural unit, etc. The (meth)acrylic resin having a ring structure in the main chain may contain only one type of ring structural unit or two or more types of ring structural units.
[0040] The following general formula (1) represents a glutaric anhydride structural unit and a glutarimide structural unit.
[0041] [Chemical formula 1]
[0042]
[0043] R in the general formula (1) 1 , R 2 are independently a hydrogen atom or a methyl group. 1 is an oxygen atom or a nitrogen atom. 1 When it is an oxygen atom, R 3 does not exist. When X 1 When it is a nitrogen atom, R 3 is a hydrogen atom, a straight-chain alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group or a phenyl group. 1 When X is an oxygen atom, the general formula (1) represents a glutaric anhydride structural unit. 1 When it is a nitrogen atom, the general formula (1) represents a glutarimide structural unit.
[0044] The following general formula (2) represents a maleic anhydride structural unit and an N-substituted maleimide structural unit.
[0045] [Chemical formula 2]
[0046]
[0047] R in the general formula (2) 4 , R 5 are independently a hydrogen atom or a methyl group. 2 is an oxygen atom or a nitrogen atom. 2 When it is an oxygen atom, R 6 does not exist. When X 2 When it is a nitrogen atom, R 6 is a hydrogen atom, a straight-chain alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group or a phenyl group. 2 When X is an oxygen atom, the general formula (2) represents a maleic anhydride structural unit. 2 When it is a nitrogen atom, the general formula (2) represents an N-substituted maleimide structural unit.
[0048] The following general formula (3) represents a lactone ring structural unit.
[0049] [Chemical formula 3]
[0050]
[0051] In the general formula (3), R 7 , R 8 and R 9 They are independently a hydrogen atom or an organic group having 1 to 20 carbon atoms. The organic group may contain an oxygen atom.
[0052] The organic group is an alkyl group, an unsaturated aliphatic hydrocarbon group, an aromatic hydrocarbon group, etc. The alkyl group is, for example, a group having 1 to 20 carbon atoms, specifically, a methyl group, an ethyl group, a propyl group, etc. The unsaturated aliphatic hydrocarbon group is, for example, a group having 2 to 20 carbon atoms, specifically, a vinyl group, a propenyl group, etc. The aromatic hydrocarbon group is, for example, a group having 6 to 20 carbon atoms, specifically, a phenyl group, a naphthyl group, etc. In the alkyl group, the unsaturated aliphatic hydrocarbon group, and the aromatic hydrocarbon group, one or more hydrogen atoms are optionally substituted by at least one group selected from a hydroxyl group, a carboxyl group, an ether group, and an ester group.
[0053] The lactone ring structural unit represented by the general formula (3) can be formed, for example, by subjecting a copolymer of methyl (meth)acrylate and methyl 2-(hydroxymethyl)acrylate to dealcoholization and cyclocondensation within the molecule.
[0054] The lactone ring structural unit represented by the general formula (3) can be said to be a lactone ring structural unit in which two or more carbon atoms among the carbon atoms constituting the lactone ring structure form the main chain of the (meth)acrylic resin. The general formula (3) shows a 6-membered lactone ring structural unit, and the number of ring members of the lactone ring may be 4 to 8. From the viewpoint of excellent stability of the ring structure, the number of ring members of the lactone ring is preferably 5 to 6.
[0055] The following general formula (4) represents another lactone ring structural unit.
[0056] [Chemical formula 4]
[0057]
[0058] R in the general formula (4) 10 ~R 13 are independently a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms. The hydrocarbon group is an aliphatic hydrocarbon group or an aromatic hydrocarbon group. An example of an aliphatic hydrocarbon group is an alkyl group. An alkyl group is a group having 1 to 10 carbon atoms, and may be a straight chain structure, a branched chain structure, or a cyclic structure. Specifically, it may be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, a cyclopentyl group, a cyclohexyl group, etc. Specifically, an aromatic hydrocarbon group may be a phenyl group, a tolyl group, a benzyl group, etc. R 10 ~R 13 Preferably, they are independently hydrogen atoms or alkyl groups having 1 to 10 carbon atoms, and more preferably, all of them are hydrogen atoms.
[0059] The lactone ring structural unit represented by the general formula (4) can be formed by polymerizing a compound represented by the following formula (5).
[0060] [Chemical formula 5]
[0061]
[0062] R in the general formula (5) 10 ~R 13 With R in the general formula (4) 10 ~R 13 same.
[0063] The lactone ring structural unit represented by the general formula (4) can be said to be a lactone ring structural unit in which one of the carbon atoms constituting the lactone ring structure forms the main chain of the (meth)acrylic resin. The general formula (4) shows a 5-membered lactone ring structural unit, and the number of ring members of the lactone ring may be 4 to 8. From the viewpoint of excellent stability of the ring structure, the number of ring members of the lactone ring is preferably 5 to 6.
[0064] The (meth) acrylic resin having a ring structure in the main chain preferably comprises at least one ring structure unit selected from the group consisting of glutaric anhydride structure unit, glutarimide structure unit, maleic anhydride structure unit, N-substituted maleimide structure unit and lactone ring structure unit, and more preferably comprises at least one ring structure unit selected from the group consisting of glutarimide structure unit and lactone ring structure unit. In other words, the (meth) acrylic resin having a ring structure in the main chain preferably has at least one ring structure selected from the group consisting of glutaric anhydride structure, glutarimide structure, maleic anhydride structure, N-substituted maleimide structure and lactone ring structure in the main chain, and more preferably has at least one ring structure selected from the group consisting of glutarimide structure and lactone ring structure.
[0065] The (meth) acrylic resin having a ring structure in the main chain may also contain a third structural unit different from the (meth) acrylic ester unit and the ring structural unit. The third structural unit is a structural unit derived from a monomer that can be copolymerized with the monomer used to form the (meth) acrylic ester unit and the ring structural unit. Specifically, it can be a structural unit derived from the following monomers: styrene, vinyl toluene, α-methyl styrene, α-hydroxymethyl styrene, α-hydroxyethyl styrene, acrylonitrile, methacrylonitrile, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, N-vinyl carbazole, etc. The (meth) acrylic resin having a ring structure in the main chain may contain only one third structural unit, or may contain two or more third structural units.
[0066] The content of each structural unit in the (meth) acrylic resin having a ring structure in the main chain is not particularly limited, and is preferably as follows. The content of the (meth) acrylic ester unit can be, for example, 50 to 99% by mass, preferably 65 to 90% by mass, and more preferably 65 to 85% by mass. The content of the ring structural unit can be, for example, 1 to 50% by mass, preferably 10 to 35% by mass, and more preferably 15 to 35% by mass. The content of the third structural unit can be, for example, 0 to 20% by mass. It should be noted that the content of each structural unit in the (meth) acrylic resin having a ring structure in the main chain is obtained as follows: the copolymer is dissolved in a deuterated solvent, and the content is measured. 1 H-NMR, the area ratio of the peak corresponding to each structural unit was calculated.
[0067] The (meth)acrylic resin having a ring structure in the main chain may be a block copolymer or a graft copolymer.
[0068] An example of a block copolymer is a block copolymer having a XYX or XY structure having a block X composed of a (meth)acrylic resin having a ring structure in the main chain and a block Y composed of an aliphatic acrylate such as butyl acrylate.
[0069] An example of a graft copolymer is a (meth) acrylic resin having a ring structure in the main chain, into which a polymer having units derived from dienes and / or olefins is introduced as a graft chain. Specifically, the polymer having units derived from dienes and / or olefins may be: styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer, hydrogenated products of styrene-butadiene-styrene block copolymer (e.g., styrene-ethylene / butylene-styrene block copolymer, styrene-butadiene / butylene-styrene block copolymer), styrene-isoprene block copolymer, styrene-isoprene-styrene block copolymer, and hydrogenated products of styrene-isoprene-styrene block copolymer (e.g., styrene-ethylene / propylene-styrene block copolymer), etc.
[0070] The weight average molecular weight (Mw) of the (meth)acrylic resin having a ring structure in the main chain may be, for example, 10,000 to 500,000, or 50,000 to 300,000.
[0071] The content of the (meth)acrylic resin having a ring structure in the main chain in the (meth)acrylic resin composition may be more than 50% by mass, preferably 70% by mass or more, and more preferably 90% by mass or more.
[0072] The (meth)acrylic resin composition may also contain a thermoplastic resin (other thermoplastic resin) different from the (meth)acrylic resin having a ring structure in the main chain. Other thermoplastic resins may be: acrylic resins, styrene resins, polycarbonate resins, polyvinylidene fluoride resins, etc. Acrylic resins may specifically include: polymethyl methacrylate, polymethyl methacrylate-styrene copolymer (MS resin), partially hydrogenated MS resin obtained by partially hydrogenating the aromatic ring of MS resin, etc. Styrene resins may specifically include: polystyrene, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer, etc.
[0073] The content of the thermoplastic resin different from the (meth)acrylic resin having a ring structure in the main chain in the (meth)acrylic resin composition is less than 50% by mass, preferably 30% by mass or less, and more preferably 10% by mass or less. The (meth)acrylic resin composition may contain only the (meth)acrylic resin having a ring structure in the main chain as a resin component.
[0074] The (meth)acrylic resin composition preferably contains an ultraviolet absorber. The ultraviolet absorber may be, for example, a triazine ultraviolet absorber, a triazole ultraviolet absorber, a benzophenone ultraviolet absorber, a salicylate ultraviolet absorber, a benzoate ultraviolet absorber, etc. The (meth)acrylic resin layer may contain only one ultraviolet absorber or may contain two or more ultraviolet absorbers. The ultraviolet absorber preferably contains at least one selected from a triazine ultraviolet absorber and a triazole ultraviolet absorber.
[0075] The triazine-based ultraviolet absorber can be specifically: 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2 UV absorbers having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkoxy-2-hydroxypropoxy)-5-α-cumylphenyl]-s-triazine skeleton (alkoxy: long-chain alkoxy such as octyloxy, nonyloxy, decyloxy, etc.)
[0076] The triazole ultraviolet absorber can be specifically: 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl )phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidomethyl)phenol, reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300, 2-(2H-benzotriazol-2-yl)-6-(straight chain and side chain dodecyl)-4-methylphenol, etc.
[0077] The ultraviolet absorber may be a commercially available product. Commercially available products include "Tinuvin (registered trademark) 326" (2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol) manufactured by BASF Japan Co., Ltd. and "ADK STAB (registered trademark) LA-31" (2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol]) manufactured by ADEKA Co., Ltd.
[0078] The content of the ultraviolet absorber in the (meth)acrylic resin composition is not particularly limited, but is preferably 0.1 to 5% by mass, and more preferably 1 to 4% by mass.
[0079] The (meth)acrylic resin composition may also contain additives such as stabilizers, processing aids, plasticizers, impact resistance aids, phase difference adjusters, matting agents, antibacterial agents, antifungal agents, antistatic agents, etc. The content of the additives in the (meth)acrylic resin composition can be appropriately adjusted, and is generally about 0.1 to 40% by weight in total.
[0080] The glass transition temperature Tgc of the (meth)acrylic resin composition is not particularly limited, but is preferably 115°C or higher from the viewpoint of making the heat resistance of the optical film better, and is preferably 160°C or lower from the viewpoint of facilitating stretching in the production of the optical film, that is, preferably 115°C or higher and 160°C or lower.
[0081] The glass transition temperature Tgc of the (meth)acrylic resin composition can be adjusted, for example, by the content of the ring structural unit in the (meth)acrylic resin having a ring structure in the main chain. If the content of the ring structural unit in the (meth)acrylic resin having a ring structure in the main chain increases, the glass transition temperature Tgc of the (meth)acrylic resin composition tends to increase.
[0082] (first outermost layer and second outermost layer)
[0083] The first outermost layer is formed of a first resin composition. The second outermost layer is formed of a second resin composition. The same description can be applied to the first resin composition and the second resin composition, so in the following description, the two are not distinguished and are simply referred to as the resin composition of the outermost layer. In addition, the same description can be applied to the first outermost layer and the second outermost layer, so in the following description, the two are not distinguished and are simply referred to as the outermost layer.
[0084] The resin composition of the outermost layer includes a resin. As for the resin, there is no particular limitation as long as the glass transition temperature of the resin composition of the outermost layer is higher than the glass transition temperature of the (meth)acrylic resin composition of the intermediate layer. The resin composition of the outermost layer may include, for example, a (meth)acrylic resin having a ring structure in the main chain, or may include a polycarbonate resin.
[0085] The case where the resin composition of the outermost layer includes a (meth) acrylic resin having a ring structure in the main chain is described. The (meth) acrylic resin having a ring structure in the main chain that can be included in the resin composition of the outermost layer can be the resin exemplified as the (meth) acrylic resin having a ring structure in the main chain that can be included in the (meth) acrylic resin composition of the intermediate layer. The resin composition of the outermost layer can also include a thermoplastic resin (other thermoplastic resin) different from the (meth) acrylic resin having a ring structure in the main chain. The other thermoplastic resin can be the resin exemplified as the other thermoplastic resin that can be included in the (meth) acrylic resin composition of the intermediate layer.
[0086] The content of the (meth)acrylic resin having a ring structure in the main chain in the resin composition of the outermost layer is preferably more than 50% by mass, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0087] The content of other thermoplastic resins in the resin composition of the outermost layer is preferably less than 50% by mass, more preferably 30% by mass or less, and further preferably 10% by mass or less. The resin composition of the outermost layer may contain only a (meth)acrylic resin having a ring structure in the main chain as a resin component.
[0088] As an example, the resin compositions of the two outermost layers may respectively contain a (meth)acrylic resin having a ring structure in the main chain. The (meth)acrylic resin contained in the two outermost layers may be a (meth)acrylic resin of the same type as the (meth)acrylic resin contained in the (meth)acrylic resin composition of the middle layer. "The same type of (meth)acrylic resin" refers to a (meth)acrylic resin of the same classification of the ring structure of the main chain. For example, the resin compositions of the two outermost layers and the (meth)acrylic resin composition of the middle layer may both contain a (meth)acrylic resin having a lactone ring structure in the main chain. Alternatively, the resin compositions of the two outermost layers and the (meth)acrylic resin composition of the middle layer may both contain a (meth)acrylic resin having a glutarimide structure in the main chain.
[0089] Furthermore, it is preferred that the contents of the ring structures in the (meth)acrylic resins having a ring structure in the main chain contained in the resin compositions of the two outermost layers are greater than the contents of the ring structures in the (meth)acrylic resins having a ring structure in the main chain contained in the (meth)acrylic resin composition of the intermediate layer.
[0090] As another example, the resin compositions of the two outermost layers may respectively contain a (meth)acrylic resin having a ring structure in the main chain. The (meth)acrylic resin contained in the two outermost layers may be a (meth)acrylic resin of a different type from the (meth)acrylic resin contained in the (meth)acrylic resin composition of the middle layer. "Different types of (meth)acrylic resins" refer to (meth)acrylic resins with different classifications of the ring structures of the main chains. For example, the resin compositions of the two outermost layers may contain a (meth)acrylic resin having a glutarimide structure in the main chain, while the (meth)acrylic resin composition of the middle layer may contain a (meth)acrylic resin having a lactone ring structure in the main chain. Alternatively, the resin compositions of the two outermost layers may contain a (meth)acrylic resin having a lactone ring structure in the main chain, while the (meth)acrylic resin composition of the middle layer may contain a (meth)acrylic resin having a glutarimide structure in the main chain.
[0091] Furthermore, it is preferred that the contents of the ring structures in the (meth)acrylic resins having a ring structure in the main chain contained in the resin compositions of the two outermost layers are greater than the contents of the ring structures in the (meth)acrylic resins having a ring structure in the main chain contained in the (meth)acrylic resin composition of the intermediate layer.
[0092] The case where the resin composition of the outermost layer includes a polycarbonate resin is described. The polycarbonate resin that can be included in the resin composition of the outermost layer can be a conventionally known polycarbonate resin. The polycarbonate resin can be any polycarbonate resin in which the structural units constituting the resin are bonded by carbonate groups. Generally, the structural units derived from dihydroxy compounds are bonded by carbonate groups. The dihydroxy compound can be an aromatic dihydroxy compound, an aliphatic dihydroxy compound, etc.
[0093] Specifically, the aromatic dihydroxy compound may be biphenols (e.g., 4,4'-dihydroxybiphenyl, 3,3',5,5'-tetramethyl-4,4'-dihydroxybiphenyl), bisphenols {e.g., bis(hydroxyphenyl)alkanes [e.g., 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy- Bis(hydroxyphenyl) C1-10 alkanes [e.g., bis(hydroxyphenyl) cycloalkanes], such as bis(hydroxyphenyl) cycloalkanes [e.g., bis(hydroxyphenyl) cycloalkanes], ...], bis(hydroxyphenyl) cycloalkanes], bis(hydroxyphenyl) cycloalkanes], bis(hydroxyphenyl) cycloalkanes], bis(hydroxyphenyl) cycloalkanes], bis(hydroxyphenyl) such as bis(hydroxyphenyl) C4-20 cycloalkanes such as 1,1-bis(4-hydroxyphenyl)cyclohexane], bis(hydroxyphenyl) sulfones [such as bis(4-hydroxyphenyl) sulfone, 2,4'-dihydroxydiphenyl sulfone], bis(hydroxyphenyl) ethers [such as 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 4,4'-dihydroxy-2,5-diethoxydiphenyl ether], bis(hydroxyphenyl) sulfides [such as bis(4-hydroxyphenyl) sulfone, 2,4'-dihydroxydiphenyl sulfone ...
[0063] The invention also includes bis(hydroxyphenyl) sulfides, bis(hydroxyphenyl) ketones [such as bis(4-hydroxyphenyl) ketone], dihydroxy compounds having a fluorene skeleton {such as bis(hydroxyphenyl) fluorenes [such as 9,9-bis(4-hydroxyphenyl) fluorene]}, bis(hydroxyalkoxy) fluorenes {such as 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy-2-methyl)phenyl]fluorene, and 9,9-bis[(hydroxy C2-4 alkoxy)phenyl]fluorene}, etc.
[0094] The aliphatic dihydroxy compound may be an alicyclic dihydroxy compound [e.g., an alicyclic dihydroxy compound having 70 or less carbon atoms, an alicyclic dihydroxy compound having a 5-membered ring or a 6-membered ring structure, an alicyclic dihydroxy compound having 70 or less carbon atoms and a 5-membered ring or a 6-membered ring structure, etc.], a non-alicyclic dihydroxy compound, etc.
[0095] Specifically, the alicyclic dihydroxy compound may be: cycloalkanediols {e.g., mono (monocyclic) cycloalkanediols [e.g., cyclohexanediols (e.g., 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 2-methyl-1,4-cyclohexanediol) and other C4-10 (mono) cycloalkanediols)], poly (polycyclic) cycloalkanediols [e.g., tricyclodecanediol, pentacyclopentadecanediol, decahydronaphthalene diol], alcohol (or tricyclotetradecanediol, for example, 2,6-decalinanediol, 1,5-decalinanediol, 2,3-decalinanediol), norbornanediol (for example, 2,3-norbornanediol, 2,5-norbornanediol), adamantanediol (for example, 1,3-adamantanediol), etc.], etc.}, di(hydroxyalkyl)cycloalkanes {for example, mono(monocyclic)cycloalkanediols [for example, cyclohexanedimethanols ( For example, C4-10 (mono) cycloalkanediC1-4 alkanols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol), etc.], poly (polycyclic) cycloalkanediols or cross-linked cyclic cycloalkanediols [for example, tricyclodecane dimethanol, pentacyclopentadecanedimethanol, decahydronaphthalenedimethanol (or tricyclotetradecane dimethanol, such as 2,6-decahydronaphthalenedimethanol, 1,5-decahydronaphthalenedimethanol, 2,3-decahydronaphthalenedimethanol), norbornane dimethanol (such as 2,3-norbornane dimethanol, 2,5-norbornane dimethanol), adamantane dimethanol (such as 1,3-adamantanedimethanol)], etc.}, heterocyclic aliphatic dihydroxy compounds {for example, heteromonocyclic aliphatic dihydroxy compounds (such as tetrahydrofuran-2,2-dimethanol, etc.), heteropolycyclic aliphatic dihydroxy compounds, etc.}, etc.
[0096] Non-alicyclic dihydroxy compounds can be, for example, alkanediols (e.g., ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,5-heptanediol, 1,6-hexanediol and other C2-20 alkanediols), polyalkylene glycols (e.g., diethylene glycol, triethylene glycol, tetraethylene glycol and other poly-C2-6 alkanediols), etc.
[0097] The polycarbonate resin may contain only one type of structural unit derived from the above-mentioned dihydroxy compound, or may contain two or more types of structural units derived from the above-mentioned dihydroxy compound.
[0098] The resin composition of the outermost layer may also contain a thermoplastic resin (other thermoplastic resin) different from the polycarbonate resin. The other thermoplastic resin may be an acrylic resin, a styrene resin, etc. The acrylic resin may specifically include polymethyl methacrylate, polymethyl methacrylate-styrene copolymer (MS resin), and a partially hydrogenated MS resin obtained by partially hydrogenating the aromatic ring of the MS resin. The styrene resin may specifically include polystyrene, styrene-methyl methacrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer, etc.
[0099] The content of the polycarbonate resin in the resin composition of the outermost layer is preferably more than 50% by mass, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0100] The content of other thermoplastic resins in the resin composition of the outermost layer is preferably less than 50% by mass, more preferably 30% by mass or less, and further preferably 10% by mass or less. The resin composition of the outermost layer may contain only polycarbonate resin as a resin component.
[0101] The outermost resin composition contains hard particles. Hard particles refer to inorganic particles and organic particles that do not have a glass transition temperature below 0°C. Hard particles are so-called anti-blocking particles, which form tiny concave and convex shapes on the surface of the optical film to improve the anti-blocking property of the optical film. It should be noted that the glass transition temperature is determined by the starting point method.
[0102] Specifically, inorganic particles may be particles composed of silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. Specifically, organic particles may be particles composed of silicone resin, fluororesin, (meth) acrylic cross-linked particles, etc. The outermost resin composition may contain only one hard particle, or may contain two or more hard particles. The outermost resin composition preferably contains at least one selected from silicon dioxide particles and (meth) acrylic cross-linked particles, and more preferably contains silicon dioxide particles.
[0103] Inorganic particles may also be commercially available products. Commercially available products include "SEAHOSTAR (registered trademark) KE series" manufactured by Nippon Shokubai Co., Ltd. Organic particles may also be commercially available products. Commercially available products include "EPOSTAR (registered trademark) MX series" and "EPOSTAR (registered trademark) MV series" manufactured by Nippon Shokubai Co., Ltd.
[0104] From the viewpoint of making the haze value and lubricity of the optical film better, the content of the hard particles in the resin composition of the outermost layer is preferably 0.001 to 1.00 mass %, more preferably 0.01 to 0.20 mass %, and further preferably 0.05 to 0.15 mass %. From the viewpoint of making the haze value and lubricity of the optical film better, the average primary particle size (median particle size) of the hard particles is preferably 0.1 to 2.0 μm, and more preferably 0.5 to 2.0 μm.
[0105] The (meth)acrylic resin composition of the intermediate layer described above may contain hard particles, but preferably contains no hard particles from the viewpoint of improving the haze value of the optical film.
[0106] The resin composition of the outermost layer may contain the usual additives that the (meth)acrylic resin composition of the intermediate layer may contain as described above. However, the resin composition of the outermost layer preferably does not contain an ultraviolet absorber.
[0107] The difference in glass transition temperature between the resin composition of the outermost layer and the (meth)acrylic resin composition of the intermediate layer is preferably 3° C. or more. When the resin composition of the outermost layer comprises a (meth)acrylic resin having a ring structure in the main chain, the difference in glass transition temperature is preferably 10° C. or less. When the resin composition of the outermost layer comprises a polycarbonate resin, the difference in glass transition temperature is preferably 21° C. or less.
[0108] The resin compositions of the two outermost layers may have different compositions as long as they are within the above ranges, but preferably have the same composition. In this way, the pair of main surfaces of the optical film have equal thermal expansion coefficients, so the optical film is less likely to warp.
[0109] [Method for producing optical film]
[0110] The optical film can be manufactured, for example, by co-extrusion. In co-extrusion, a venting extruder equipped with a single screw or a twin screw extrusion screw can be used. For example, two extruders are used, and the resin composition for forming the intermediate layer and the resin composition for forming the first outermost layer and the second outermost layer are put into separate melt extrusion devices to obtain a resin composition in a molten state. It should be noted that, when the composition of the first outermost layer and the second outermost layer is different, three extruders can be used.
[0111] The resin composition in the molten state is extruded into a film-like shape by the following method: after being measured with a gear pump respectively, after being stacked using a sleeve (pinole) and a feed block (feed block), a method of discharging using a T die orifice; a method of discharging using a multi-manifold die orifice, etc. At this time, from the viewpoint of suppressing coloration, it is preferred to use a vent provided at an extruder to carry out melt mixing under reduced pressure, or to carry out melt mixing under a nitrogen stream. In addition, from the viewpoint of suppressing the number of foreign matter, the resin composition in the molten state is preferably filtered with a filter after being measured with a gear pump.
[0112] The extruded resin composition is cooled and solidified by a casting drum to form an unstretched film. At this time, in order to prevent the unstretched film from forming unevenness (so-called die lines, etc.), the casting drum is preferably pressed by a metal nip roller, an elastic metal nip roller having a metal sleeve on a rubber roller, or the like.
[0113] The unstretched film is stretched while being heated to form an optical film. The stretching temperature is set based on the glass transition temperature of the resin composition constituting the unstretched film. In particular, in the manufacture of optical films with a multilayer structure, the glass transition temperature of the resin composition that mainly constitutes the intermediate layer of the optical film is usually used as a reference for setting. From this point of view, the stretching temperature, for example, based on the glass transition temperature Tgc of the resin composition of the intermediate layer, can be about (Tgc+20)°C. The stretching method can be uniaxial stretching or biaxial stretching (sequential biaxial stretching, simultaneous biaxial stretching). The stretching ratio can be, for example, about 2 times. The stretching speed can be, for example, about 1m / min.
[0114] The obtained optical film can be wound around a cylindrical core to form an optical film roll.
[0115] [Characteristics of optical films]
[0116] As described above, the resin compositions of the two outermost layers each contain hard particles, thereby forming irregularities on the surfaces of the two outermost layers. As a result, the optical film has excellent lubricity.
[0117] In addition, the glass transition temperature of the resin composition of the two outermost layers is higher than the glass transition temperature of the (meth) acrylic resin composition of the middle layer, so that the two outermost layers are not easily softened excessively when the optical film is manufactured. Therefore, when the optical film is manufactured, the retention force of the hard particles in the two outermost layers is fully maintained, and the graining is suppressed. Furthermore, the slipperiness of the optical film is stabilized.
[0118] Furthermore, the (meth)acrylic resin composition of the intermediate layer may contain a UV absorber, while the resin compositions of the two outermost layers may not contain a UV absorber. In this way, bleeding of the UV absorber can be further suppressed.
[0119] In addition, the resin composition of the two outermost layers may respectively contain a (meth) acrylic resin having a ring structure in the main chain. The (meth) acrylic resin contained in the two outermost layers may be a (meth) acrylic resin of the same type as the (meth) acrylic resin contained in the (meth) acrylic resin composition of the middle layer. It can be set that the content of the ring structure in the (meth) acrylic resin contained in the resin composition of the two outermost layers is greater than the content of the ring structure in the (meth) acrylic resin contained in the (meth) acrylic resin composition of the middle layer. In this way, the glass transition temperature of the resin composition of the two outermost layers can be easily higher than the glass transition temperature of the (meth) acrylic resin composition of the middle layer. In addition, the two outermost layers and the middle layer are both (meth) acrylic resin compositions, so not only can high transparency be maintained, but also the adhesion of each layer is good.
[0120] In addition, the resin compositions of the two outermost layers may respectively contain a (meth) acrylic resin having a ring structure in the main chain. The (meth) acrylic resin contained in the two outermost layers may be a (meth) acrylic resin of a different type from the (meth) acrylic resin contained in the (meth) acrylic resin composition of the middle layer. In this way, the glass transition temperature of the resin composition of the two outermost layers can be easily higher than the glass transition temperature of the (meth) acrylic resin composition of the middle layer. On this basis, the content of the ring structure in the (meth) acrylic resin contained in the resin composition of the two outermost layers can be set to be greater than the content of the ring structure in the (meth) acrylic resin contained in the (meth) acrylic resin composition of the middle layer. In this way, the glass transition temperature of the resin composition of the two outermost layers can be more easily higher than the glass transition temperature of the (meth) acrylic resin composition of the middle layer. In addition, the two outermost layers and the middle layer are both (meth) acrylic resin compositions, so not only can high transparency be maintained, but also the adhesion of each layer is good.
[0121] In addition, the two outermost layers may also contain polycarbonate resins respectively. In this way, the glass transition temperature of the resin composition of the two outermost layers can be easily made higher than the glass transition temperature of the (meth) acrylic resin composition of the middle layer. In addition, the outermost layer of the optical film contains polycarbonate resin, so the mechanical properties of the optical film are better.
[0122] [Application of optical film]
[0123] The optical film of one embodiment of the present disclosure is suitable for use as, for example, a polarizer protective film or a phase difference film, and is more suitable for use as a polarizer protective film. The polarizer protective film is a film that can be included in a polarizing plate included in an image display device.
[0124] That is, the present disclosure includes not only the optical film of one embodiment but also a polarizing plate protective film including the optical film of one embodiment, a polarizing plate including the polarizing plate protective film, and an image display device including the polarizing plate.
[0125] The optical film of one embodiment of the present disclosure is also suitable for use in zero phase difference film, viewing angle compensation film, light diffusion film, reflective film, anti-reflective film, anti-glare film, brightness enhancement film, conductive film for touch panel, diffuser plate, light guide, phase difference plate, zero phase difference plate, prism sheet, etc.
[0126] Example
[0127] The embodiments of the present disclosure are described. Of course, the present disclosure is not limited to the following embodiments.
[0128] [Measurement method]
[0129] Prior to the description of Examples, the evaluation method of the optical film will be described.
[0130] (1) Weight average molecular weight (Mw)
[0131] The weight average molecular weight was determined by polystyrene conversion using gel permeation chromatography (GPC). The device and measurement conditions used for the measurement are as follows.
[0132] -System: GPC system HLC-8220 manufactured by TOSOH Corporation.
[0133] - Determine the side column composition
[0134] Guard column: manufactured by TOSOH, TSKguardcolumn SuperHZ-L.
[0135] Separation column: Two TSKgel SuperHZM-M columns manufactured by TOSOH were connected in series.
[0136] - Reference jamb composition
[0137] Reference column: TSKgel SuperH-RC manufactured by TOSOH Corporation.
[0138] -Developing solvent: chloroform (manufactured by FUJIFILM Wako Pure Chemical Co., Ltd., special grade).
[0139] -Flow rate of developing solvent: 0.6 mL / min.
[0140] - Standard sample: TSK standard polystyrene (manufactured by TOSOH, PS-Oligomer Kit).
[0141] - Column temperature: 40°C.
[0142] (2) Glass transition temperature
[0143] The glass transition temperature was determined according to the provisions of Japanese Industrial Standard (JIS) K 7121. It was determined by the starting point method based on the DSC curve obtained by heating about 10 mg of a sample from room temperature to 200° C. (heating rate 20° C. / min) under a nitrogen atmosphere using a differential scanning calorimeter (Rigaku Corporation, Thermo plus EVO DSC-8230). It should be noted that α-alumina was used as a reference.
[0144] (3)Thickness of optical film
[0145] The thickness of the optical film was determined using a digital micrometer (manufactured by Mitutoyo Co., Ltd.). The thickness of the intermediate layer and the outermost layer constituting the optical film was determined by observing the cross section of the optical film using a scanning electron microscope (manufactured by Hitachi High-Technologies (currently Hitachi High-Tech Co., Ltd.), FE-SEM S-4800). It should be noted that the measurement conditions were set to an acceleration voltage of 20 kV, an emission current of 5 μA or 10 μA, and WD = 8 mm.
[0146] (4) Slipperiness
[0147] The slipperiness of the optical film is determined according to the provisions of Japanese Industrial Standard (JIS) K 7125. First, an optical film cut into a size of 80 mm × 100 mm is fixed on a stainless steel plate so that the surface is kept horizontal in a manner that the second outermost layer contacts the stainless steel plate. Next, an optical film cut into a size of 70 mm × 100 mm with an auxiliary plate installed on the short side is placed on the fixed film, and a cylindrical weight (540 g, diameter 62 mm) with a cushioning material of 2 mm thickness is placed thereon. In this state, a spring balance is installed on the auxiliary plate, and the installed spring balance is pulled horizontally at a speed of 300 mm / min. The maximum load displayed by the spring balance until the weight starts to move, that is, the optical films start to slide against each other, is measured and used as the slipperiness of the optical film. The higher the slipperiness of the optical film, the smaller the value of the measured maximum load.
[0148] (5) Threshing resistance
[0149] The surface of the first outermost layer of the optical film was observed by a scanning electron microscope (acceleration voltage 5 kV, secondary electron image). The observation magnification was set to 500 times, and the size of one field of view was set to 270 μm × 200 μm for shooting. While moving the observation location so as not to shoot the same location, 25 fields of view were shot, and the detachment marks of particles contained in each shot image were counted and the average was calculated. The evaluation is as follows.
[0150] ○: The number of peeling marks is 0 to 10.
[0151] ×: The number of the falling marks was 11 or more.
[0152] (6) Haze value
[0153] The haze value of the optical film was determined using a turbidity meter ("NDH-5000" manufactured by Nippon Denshoku Industries, Ltd.) in accordance with the provisions of Japanese Industrial Standards (JIS) K 7136.
[0154] (7) Stretchability
[0155] [A Breaking resistance during tension]
[0156] The case where the film can be stretched for 2 hours or more without breaking in both the longitudinal stretching step and the transverse stretching step was set to 0. The case where breaking occurred in less than 2 hours in at least one of the longitudinal stretching step and the transverse stretching step was set to ×.
[0157] [B Uniformity of film thickness]
[0158] A projector (Polarion Light (manufactured by CSC Co., Ltd., NP-1, 3400 lumens)) was set at a distance of 1 m from the white mesh to irradiate the white mesh with light. An optical film was placed at a 45° inclination relative to the surface of the white mesh on the irradiation line of the light and at a distance of 15 cm from the mesh. The projected image of the optical film presented on the white mesh at this time was visually evaluated. The evaluation was as follows.
[0159] S: Case where no fringe pattern is observed in the projected image.
[0160] A: A case where a stripe pattern with weak contrast is observed in the projected image.
[0161] B: A case where a stripe pattern with strong contrast is observed in the projected image.
[0162] Qualified: It is the case of S or A.
[0163] Unqualified: This is the situation of B.
[0164] [Uniformity of C phase difference]
[0165] The optical film was cut into A4 size and visually observed under crossed Nicol prisms. It should be noted that the optical film was set at an angle of 45° with the long dimension direction (MD) and the absorption axis of the front polarizing plate when the optical film was manufactured, and the contrast was observed at the highest state during visual observation. The evaluation was as follows.
[0166] S: No color unevenness was observed.
[0167] A: Color unevenness with weak contrast is observed.
[0168] B: Color unevenness with strong contrast is observed.
[0169] Qualified: It is the case of S or A.
[0170] Unqualified: This is the situation of B.
[0171] [Example]
[0172] [Manufacture of Resin Composition 1A]
[0173] Into a reaction vessel equipped with a stirring device, a temperature sensor, a cooling tube and a nitrogen introduction tube, 229.6 parts by mass of methyl methacrylate (MMA), 33 parts by mass of methyl 2-(hydroxymethyl)acrylate (MHMA), 248.6 parts by mass of toluene and 0.19 parts by mass of n-dodecyl mercaptan were charged, nitrogen was introduced therein, and the temperature was raised to 105°C. At the start of reflux accompanied by temperature rise, 0.25 parts by mass of tert-amyl peroxy isononanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: Luperox (registered trademark) 570) was added as a polymerization initiator. Next, 0.51 parts by mass of tert-amyl peroxy isononanoate and 12.4 parts by mass of styrene were added dropwise over 2 hours. During the period of dropping them, the solution was refluxed at about 105-110°C to perform solution polymerization. After the dropwise addition was completed, aging was further performed at the same temperature for 4 hours.
[0174] To the obtained polymerization solution, 0.21 parts by mass of stearyl phosphate (manufactured by Sakai Chemical Industry Co., Ltd., trade name: Phoslex A-18) was added, and a cyclization condensation reaction for forming a lactone structure was carried out under reflux at about 90 to 110° C. for 1.5 hours.
[0175] Furthermore, the polymerization solution is passed through a multi-tubular heat exchanger heated to 240°C to complete the cyclization condensation reaction. Then, the polymerization solution is introduced into a vented twin-screw extruder (L / D=52) at a processing rate of 35.1 parts by mass / hour (converted into resin amount). The barrel temperature of the vented twin-screw extruder is 250°C, and it is equipped with a rear exhaust port, four front exhaust ports (called the first exhaust port, the second exhaust port, the third exhaust port, and the fourth exhaust port from the upstream side) and a side feeder located between the third exhaust port and the fourth exhaust port, and a blade disk-type polymer filter (filtration accuracy 5μm) is arranged at the front end. When introducing the polymerization solution, a mixed solution of an antioxidant / cyclization catalyst deactivator prepared separately is added from the downstream of the second exhaust port at an injection rate of 0.15 parts by mass / hour, and ion exchange water is added from the downstream of the first exhaust port and the third exhaust port at an injection rate of 0.54 parts by mass / hour. The mixed solution of the antioxidant / cyclization catalyst deactivator was prepared by dissolving 4.3 parts by mass of an antioxidant (trade name: Irganox 1010 manufactured by BASF JAPAN Co., Ltd.; trade name: ADK STAB (registered trademark) LAO-412S manufactured by ADEKA Co., Ltd.) and 14 parts by mass of zinc octoate (trade name: Nikka Octhix Zinc manufactured by Nippon Chemical Industry Co., Ltd.) as a deactivator in 144 parts by mass of toluene. In addition, an ultraviolet absorber (trade name: ADK STAB (registered trademark) LA-31 manufactured by ADEKA Co., Ltd.) was added from the side feeder at a rate of 0.79 parts by mass / hour.
[0176] After the devolatilization is completed, the resin composition in a molten state remaining in the extruder is discharged from the front end of the extruder while being filtered with a polymer filter. Then, it is passed through the die head provided at the front end of the extruder and cooled in a water tank filled with cooling water, thereby obtaining a strand of the above-mentioned resin composition. The above-mentioned cooling water is filtered with a filter with a pore size of 1 μm (manufactured by Organo Co., Ltd., product name: microporefilter1EU) and maintained at a temperature within the range of 30±10°C. The cooled strand is introduced into a cutter (granulator) to obtain a resin composition 1A containing a (meth) acrylic resin having a lactone ring structure in the main chain. The weight average molecular weight of the obtained resin composition 1A is 149,000, and the glass transition temperature is 120°C. In addition, the content of the lactone ring structure is 19.6% by mass.
[0177] [Manufacture of Resin Composition 2A]
[0178] Into a reaction vessel equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen introduction tube, 83.5 parts by mass of methyl methacrylate (MMA), 12 parts by mass of methyl 2-(hydroxymethyl)acrylate (MHMA), 88.7 parts by mass of toluene, and 0.05 parts by mass of an antioxidant (manufactured by ADEKA Co., Ltd., trade name: ADK STAB (registered trademark) 2112) were charged, nitrogen was introduced therein, and the temperature was raised to 105°C. At the start of reflux accompanied by temperature rise, 0.435 parts by mass of a 20% by mass toluene solution of tert-amyl peroxy isononanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: Luperox (registered trademark) 570T20) was added as a polymerization initiator. Next, 4.5 parts by mass of styrene (St) and 0.15 parts by mass of n-dodecyl mercaptan (nDM) were added dropwise over 2 hours. In addition, 0.865 parts by mass of a 20% by mass toluene solution of tert-amyl peroxy isononanoate was added dropwise over 4 hours. During the dropwise addition, the mixed solution was refluxed at about 105 to 110° C. to carry out solution polymerization. After the dropwise addition was completed, aging was further carried out at the same temperature for 2 hours.
[0179] To the obtained polymerization solution was added 0.075 parts by mass of stearyl phosphate (manufactured by SC Organic Chemical Co., Ltd., trade name: Phoslex A-18), and a cyclization condensation reaction for forming a lactone structure was carried out under reflux at about 90 to 110° C. for 2 hours.
[0180] Furthermore, the polymerization solution is passed through a multi-tubular heat exchanger heated to 240°C to complete the cyclization condensation reaction. Then, the polymerization solution is introduced into a venting twin-screw extruder (L / D=52) at a processing rate of 31.2 parts by mass / hour (converted into resin amount). The barrel temperature of the venting twin-screw extruder is 250°C, and it has a rear exhaust port, four front exhaust ports (called the first exhaust port, the second exhaust port, the third exhaust port, and the fourth exhaust port from the upstream side) and a side feeder located between the third exhaust port and the fourth exhaust port, and a blade disc type polymer filter (filtration accuracy 10μm) is arranged at the front end. The decompression degree of each exhaust port is set to 798hPa for the rear exhaust port, 266hPa for the first exhaust port, and 27hPa for the second exhaust port to the fourth exhaust port, and devolatilization is implemented. At this time, ion exchange water is added from the rear of the second exhaust port and the fourth exhaust port at an input rate of 0.47 parts by mass / hour.
[0181] After the devolatilization is completed, the resin composition in a molten state remaining in the extruder is discharged from the front end of the extruder while being filtered with the above-mentioned polymer filter. Then, it is passed through the die head equipped at the front end of the extruder and cooled in a water tank filled with cooling water, thereby obtaining a strand of the above-mentioned resin composition. The above-mentioned cooling water is filtered with a filter with a pore size of 1 μm (manufactured by Organo Co., Ltd., trade name: microporefilter1EU) and maintained at a temperature within the range of 30±10°C. The cooled strand is introduced into a cutter (granulator) to obtain a resin composition 2A containing a (meth) acrylic resin having a lactone ring structure in the main chain. The weight average molecular weight of the obtained resin composition 2A is 133,000, and the glass transition temperature is 123°C. In addition, the content of the lactone ring structure is 19.6% by mass.
[0182] [Manufacture of Resin Composition 3A]
[0183] Resin composition 3A containing a (meth)acrylic resin having a lactone ring structure in the main chain was obtained in the same manner as resin composition 1A except that the ultraviolet absorber used was Tinuvin (registered trademark) 326 (manufactured by BASF Japan Co., Ltd.) The obtained resin composition 3A had a weight average molecular weight of 149,000 and a glass transition temperature of 120°C.
[0184] [Manufacture of Resin Composition 4A]
[0185] Into a reaction container equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen introduction tube, 40 parts by mass of methyl methacrylate (MMA), 10 parts by mass of methyl 2-(hydroxymethyl)acrylate (MHMA), 50 parts by mass of toluene, and 0.025 parts by mass of an antioxidant (manufactured by ADEKA Corporation, trade name: ADK STAB (registered trademark) 2112) were charged, nitrogen was introduced therein, and the temperature was raised to 105° C. At the start of reflux accompanying the temperature increase, 0.05 parts by mass of tert-amyl peroxyisononanoate (manufactured by ARKEMA Yoshitomi Co., Ltd., trade name: Luperox (registered trademark) 570T20) was added as a polymerization initiator, and solution polymerization was carried out at reflux of about 105 to 110° C. while 0.1 parts by mass of tert-amyl peroxyisononanoate was added dropwise over 2 hours, and aging was further carried out over 4 hours.
[0186] To the obtained polymer solution, 0.05 parts by mass of stearyl phosphate (manufactured by Sakai Chemical Industry Co., Ltd., trade name: Phoslex A-18) was added, and a cyclocondensation reaction was carried out under reflux at 90 to 105° C. for 2 hours.
[0187] Furthermore, the polymer solution was passed through a multi-tube heat exchanger heated to 240°C to complete the cyclization condensation reaction. Then, the polymer solution was introduced into a vented twin-screw extruder (L / D=52) at a processing rate of 90.0 parts by mass / hour (converted to the amount of resin). The barrel temperature of the vented twin-screw extruder was 240°C, the degree of decompression was 13.3-400hPa (10-300mmHg), and it was equipped with a rear exhaust port, four front exhaust ports (called the first exhaust port, the second exhaust port, the third exhaust port, and the fourth exhaust port from the upstream side) and a side feeder located between the third exhaust port and the fourth exhaust port, and a blade disk type polymer filter (filtration accuracy 5μm) was arranged at the front end. When the polymer solution was introduced, a mixed solution of an antioxidant / cyclization catalyst deactivator prepared separately was added from the downstream of the second exhaust port at an injection rate of 0.35 parts by mass / hour, and ion exchange water was added from the downstream of the first exhaust port and the third exhaust port at an injection rate of 0.54 parts by mass / hour. The mixed solution of the antioxidant / cyclization catalyst deactivator was prepared by dissolving 4.3 parts by mass of an antioxidant (trade name: Irganox 1010, manufactured by BASF JAPAN Co., Ltd.; trade name: ADK STAB (registered trademark) LAO-412S, manufactured by ADEKA Co., Ltd.) and 14 parts by mass of zinc octoate (trade name: Nikka Octhix Zinc, manufactured by Nippon Chemical Industry Co., Ltd.) as a deactivator in 144 parts by mass of toluene.
[0188] After the devolatilization is completed, the resin composition in a hot melt state remaining in the extruder is discharged from the front end of the extruder while being filtered with the above-mentioned polymer filter, and is passed through the die head of the extruder. Then, the strands are cooled in a water tank filled with cooling water, and the cooling water is filtered with a filter with a pore size of 1 μm (Organo Co., Ltd., trade name: microporefilter1EU) and maintained at a temperature within the range of 30±10°C. Then, the strands are introduced into a cutter (granulator), thereby obtaining a resin composition 4A containing a (meth) acrylic resin having a lactone ring structure in the main chain. The weight average molecular weight of the obtained resin composition 4A is 135,000, and the glass transition temperature is 131°C. In addition, the content of the lactone ring structure is 33.5% by mass.
[0189] [Manufacture of Resin Composition 5A]
[0190] A UV absorber (manufactured by ADEKA Corporation, trade name: ADK STAB (registered trademark) LA-31) was introduced into resin composition 4A by the same operation as in Production Example 1 to obtain resin composition 5A containing a (meth)acrylic resin having a lactone structure in the main chain. The obtained resin composition (5A) had a weight average molecular weight of 149,000 and a glass transition temperature of 129°C.
[0191] [Manufacture of Resin Composition 6A]
[0192] A (meth)acrylic resin having a glutarimide structure in the main chain (manufactured by Daicel-Evonik, trade name: Pleximid 8813, Tg 132° C.) was used as resin composition 6A.
[0193] [Manufacture of Resin Composition 7A]
[0194] A (meth)acrylic resin having an N-phenylmaleimide structure in the main chain (manufactured by Nippon Shokubai Co., Ltd., trade name: POLYIMILEX PML203, Tg 139° C.) was used as the resin composition 7A.
[0195] [Manufacture of resin composition 8A]
[0196] A polycarbonate resin (manufactured by Teijin Co., Ltd., trade name: Panlite L-1225Y, Tg 150° C.) was prepared as a resin composition 8A.
[0197] [Manufacture of Resin Composition 1B]
[0198] 1.0 part by mass of silica particles (refractive index 1.43, average particle size 0.3 μm, manufactured by Nippon Shokubai Co., Ltd., trade name: SEAHOSTAR (registered trademark) KE-P30) and 99 parts by mass of the resin composition 2A were melt-kneaded at 260° C. using a twin-screw extruder (manufactured by PLABOR Research Laboratory of Plastics Technology Co., Ltd., BT-30-S21C-30-1) to obtain a resin composition 1B.
[0199] [Manufacture of resin compositions 2B to 5B]
[0200] Resin composition 1B and resin composition 2A were melt-kneaded to obtain resin compositions 2B to 5B. At this time, the content (mass %) of the silica particles in resin compositions 2B to 5B was adjusted by adjusting the mixing ratio of resin composition 1B to resin composition 2A.
[0201] [Manufacture of resin compositions 6B to 10B]
[0202] Silica particles (refractive index 1.43, average particle size 0.3 μm, manufactured by Nippon Shokubai Co., Ltd., trade name: SEAHOSTAR (registered trademark) KE-P30) were melt-kneaded with resin composition 1A to obtain resin composition 6B. Similarly, silica particles were melt-kneaded with resin composition 4A, resin composition 6A, resin composition 7A, and resin composition 8A to obtain resin composition 7B, resin composition 8B, resin composition 9B, and resin composition 10B. At this time, the content (mass %) of silica particles in resin compositions 6B to 10B was adjusted by adjusting the mixing ratio of silica particles and resin composition 1A, resin composition 4A, resin composition 6A, resin composition 7A, and resin composition 8A.
[0203] [Manufacture of resin compositions 11B to 13B]
[0204] Silica particles (refractive index 1.43, average particle size 0.1 μm, manufactured by Nippon Shokubai Co., Ltd., trade name: SEAHOSTAR (registered trademark) KE-P10) were melt-kneaded with resin composition 2A to obtain resin composition 11B and resin composition 12B. Silica particles (refractive index 1.43, average particle size 0.5 μm, manufactured by Nippon Shokubai Co., Ltd., trade name: SEAHOSTAR (registered trademark) KE-P50) were melt-kneaded with resin composition 2A to obtain resin composition 13B. At this time, the content (mass %) of silica particles in resin compositions 11B to 13B was adjusted by adjusting the mixing ratio of silica particles and resin composition 2A.
[0205] [Manufacture of resin compositions 14B to 15B]
[0206] The (meth)acrylic acid crosslinked particles (refractive index 1.51, average particle size 1 μm) produced by the method described in Japanese Patent No. 4034157 were melt-kneaded with the resin composition 2A to obtain resin composition 14B. The (meth)acrylic acid crosslinked particles (refractive index 1.51, average particle size 1.2 μm) produced by the method described in the same publication were melt-kneaded with the resin composition 2A to obtain resin composition 15B. At this time, the content (mass %) of the silica particles in the resin composition 14B and the resin composition 15B was adjusted by adjusting the mixing ratio of the (meth)acrylic acid crosslinked particles and the resin composition 2A.
[0207] Table 1 shows the types of particles contained in the resin compositions 1B to 15B, the particle diameters of the particles, the content of the particles, and the glass transition temperatures of the resin compositions.
[0208] [Table 1]
[0209]
[0210] [Manufacturing of Optical Films 1 to 24]
[0211] Resin composition 1A and resin composition 1B were dried in a hot air oven at 80°C for 8 hours. In addition, single screw extruder A and single screw extruder B equipped with a blade disc type polymer filter with a filtration accuracy of 5 μm were prepared. The resin composition 1A (pellets) for obtaining the middle layer was put into the single screw extruder A, and the resin composition 1B (pellets) for obtaining the outermost layer was put into the single screw extruder B, and melt extrusion molding was performed at 270°C, and a molten film (optical film in a molten state) laminated in the order of the outermost layer, the middle layer, and the outermost layer was obtained through a feed block.
[0212] The molten film was passed through a first cooling roll adjusted to 120° C., a second cooling roll adjusted to 95° C., and a plurality of conveyor rolls in this order to obtain an unstretched film.
[0213] The unstretched film was stretched longitudinally using an oven stretching machine. Specifically, the film was heated while adjusting the peripheral speed of the roller used to transport the film to stretch the film longitudinally. The temperature during stretching was set to (Tg+16)°C (136°C in the manufacture of optical film 1) relative to the glass transition temperature Tg of the resin composition used for the intermediate layer. The stretching ratio was set to 2.2 times. The stretching method was free-end uniaxial stretching without fixing the transverse direction. The thickness of the film obtained in this way was 116 μm.
[0214] The longitudinally stretched film was stretched transversely using a tenter stretching machine. Specifically, the film was heated while being clamped at both ends of the film by 2-inch clamps at a position 20 mm from the ends, and the film was stretched transversely. The temperature during stretching was set to (Tg+23)°C (143°C in the manufacture of the optical film 1) relative to the glass transition temperature Tg of the resin composition used in the intermediate layer. The stretching ratio was set to 3.0 times. The thickness of the optical film 1 obtained in this way was 40 μm.
[0215] Optical films 2 to 24 were manufactured in the same manner as the manufacture of optical film 1, except that the combination of the resin composition (pellets) used for the intermediate layer and the outermost layer was changed and the thickness of the intermediate layer and the outermost layer was changed. It should be noted that the thickness of the intermediate layer and the outermost layer was changed by adjusting the extrusion amount of the single screw extruder A used to obtain the intermediate layer and the single screw extruder B used to obtain the outermost layer.
[0216] The combination of the resin composition (particles) of the intermediate layer and the outermost layer in the optical films 1 to 24, the difference in glass transition temperature (Tg difference) between the intermediate layer and the outermost layer, and the thickness of each intermediate layer and the outermost layer are shown in Table 2. The difference in glass transition temperature between the intermediate layer and the outermost layer represents a value obtained by subtracting the glass transition temperature of the intermediate layer from the glass transition temperature of the outermost layer.
[0217] [Table 2]
[0218]
[0219] [Evaluation of Optical Films 1 to 24]
[0220] According to the above method, the slipperiness, detachment resistance, haze value, and stretchability of the optical films 1 to 24 were evaluated. The results are shown in Table 3. Since the optical film 23 does not have particles, the detachment resistance was not measured.
[0221] [Table 3]
[0222]
[0223] The optical films 1 to 22 and 24, whose outermost layers contain silica particles or (meth)acrylic crosslinked particles, have excellent lubricity. This is considered to be because the outermost layer contains particles, thereby forming irregularities on the surface of the optical film. More specifically, it is speculated that this is because the contact area with other components is reduced compared to the case where irregularities are not formed on the surface of the optical film. On the other hand, the optical film 23, whose outermost layer does not contain particles, has poor lubricity.
[0224] Optical films 1 to 22, in which the glass transition temperature of the resin composition of the outermost layer is higher than the glass transition temperature of the resin composition of the middle layer, have excellent resistance to granulation. It is believed that this is because the glass transition temperature of the resin composition of the outermost layer is higher than the glass transition temperature of the resin composition of the middle layer, so that the outermost layer is not easy to soften excessively when manufacturing the optical film. In more detail, it is speculated that in the manufacture of the optical film (especially the stretching process), the optical film needs to be heated to a temperature above the glass transition temperature of the middle layer, which will inhibit the softening of the outermost layer at this time, thereby fully maintaining the holding force of the particles in the outermost layer. On the other hand, the optical film 24, in which the glass transition temperature of the resin composition of the outermost layer is the same as the glass transition temperature of the resin composition of the middle layer, has poor resistance to granulation.
[0225] As described above, Optical Films 1 to 22 in which the outermost layer resin composition contains hard particles and the glass transition temperature of the outermost layer resin composition is higher than the glass transition temperature of the intermediate layer resin composition are excellent in both lubricity and anti-graining properties.
[0226] According to the optical films 1 to 5 , the content of the particles may be, for example, 0.001 to 1% by mass.
[0227] According to the optical film 2, optical film 6 to optical film 10, when the thickness of the optical film is 40 μm, the thickness of an outermost layer can be 0.5 to 15 μm. Therefore, the thickness of an outermost layer can be, for example, 1.25% to 37.5% relative to the thickness of the optical film. The thickness of the intermediate layer can be, for example, 25% to 97.5% relative to the thickness of the optical film.
[0228] According to the optical film 2 and the optical films 11 to 13 , the particle diameter of the particles may be, for example, 0.1 to 0.5 μm.
[0229] Depending on the optical film 2 or the optical film 14 , the ultraviolet absorber may be “Tinuvin (registered trademark) 326” (manufactured by BASF Japan Co., Ltd.) or “ADK STAB (registered trademark) LA-31” (manufactured by ADEKA Corporation).
[0230] According to the optical film 2 or the optical film 15 , the content of the ring structure of the (meth)acrylic resin having a ring structure in the main chain contained in the resin composition of the intermediate layer may be, for example, 19 to 34% by mass.
[0231] According to the optical film 2, optical film 16 to optical film 20, the resin contained in the resin composition of the outermost layer may be a (meth) acrylic resin having a ring structure in the main chain, or a polycarbonate resin. The ring structure formed in the main chain of the (meth) acrylic resin having a ring structure in the main chain may be a lactone ring structure, an N-phenylmaleimide structure, or a glutarimide structure.
[0232] Depending on the optical film 2 , the optical films 21 to 22 , the hard particles contained in the resin composition of the outermost layer may be inorganic particles (particularly silica particles) or organic particles (particularly (meth)acrylic crosslinked particles).
[0233] Among the optical films 1 to 22, the haze values of the optical films 2 to 22 are superior to those of the optical film 1. This is considered to be because the content of particles contained in the resin composition of the outermost layer is appropriate, so the scattering of light caused by the particles is effectively suppressed. The optical film 1 contains 1% by mass of particles, and the optical films 2 to 22 contain 0.001 to 0.1% by mass of particles. Therefore, it can be said that the content of particles is preferably 0.001 to 0.1% by mass.
[0234] Among the optical films 1 to 22, the optical films 1 to 15 and the optical films 18 to 22 are superior in stretchability B and stretchability C compared to the optical films 16 to 17. This is considered to be because the difference in glass transition temperature between the resin composition of the intermediate layer and the resin composition of the outermost layer is appropriate, so the softening degree of the intermediate layer and the outermost layer in the stretching process is similar, and the stress generated between the intermediate layer and the outermost layer in the stretching process is suppressed.
[0235] Let's examine it in more detail. In the optical film whose outermost layer comprises a (meth) acrylic resin having a ring structure in the main chain, the difference in glass transition temperature between the resin composition of the intermediate layer and the resin composition of the outermost layer of Optical Films 1 to 15, Optical Films 18 to 19, and Optical Films 21 to 22 is 10°C or less, and the difference in glass transition temperature between the resin composition of the intermediate layer and the resin composition of the outermost layer of Optical Film 16 is 13°C. Therefore, it can be said that in the optical film whose outermost layer comprises a (meth) acrylic resin having a ring structure in the main chain, the difference in glass transition temperature between the resin composition of the intermediate layer and the resin composition of the outermost layer is preferably 10°C or less. The difference in glass transition temperature can be 3°C or more.
[0236] In the optical film in which the resin composition of the outermost layer includes a polycarbonate resin, the difference in glass transition temperature between the resin composition of the intermediate layer of the optical film 20 and the resin composition of the outermost layer is 21°C, and the difference in glass transition temperature between the resin composition of the intermediate layer of the optical film 17 and the resin composition of the outermost layer is 30°C. Therefore, it can be said that the difference in glass transition temperature between the resin composition of the intermediate layer and the resin composition of the outermost layer is preferably 21°C or less. It should be noted that the polycarbonate resin is easily stretched even at a temperature lower than the glass transition temperature, so it is considered that the preferred difference in glass transition temperature is larger than the case where the resin composition of the outermost layer includes a (meth) acrylic resin having a ring structure in the main chain.
Claims
1. An optical film, comprising: a first outermost layer formed of a first resin composition; a second outermost layer formed of a second resin composition; and an intermediate layer disposed between the first outermost layer and the second outermost layer, the intermediate layer being formed of a (meth)acrylic resin composition including a (meth)acrylic resin having a ring structure in the main chain, The first resin composition and the second resin composition contain hard particles, The glass transition temperature Tga of the first resin composition, the glass transition temperature Tgb of the second resin composition, and the glass transition temperature Tgc of the (meth)acrylic resin composition satisfy the following formula (A) and the following formula (B), Formula (A): Tga>Tgc; Formula (B): Tgb>Tgc.
2. The optical film according to claim 1, wherein: The (meth)acrylic resin composition comprises an ultraviolet absorber, The first resin composition and the second resin composition do not contain an ultraviolet absorber.
3. The optical film according to claim 1, wherein The first resin composition and the second resin composition each contain a (meth)acrylic resin having a ring structure in the main chain, The (meth)acrylic resin contained in the first resin composition and the second resin composition is the same type of (meth)acrylic resin as the (meth)acrylic resin contained in the (meth)acrylic resin composition, The content of the ring structure in the (meth)acrylic resin contained in the first resin composition and the second resin composition is respectively greater than the content of the ring structure in the (meth)acrylic resin contained in the (meth)acrylic resin composition.
4. The optical film according to claim 1, wherein The first resin composition and the second resin composition each contain a (meth)acrylic resin having a ring structure in the main chain, The (meth)acrylic resin contained in the first resin composition and the second resin composition is a (meth)acrylic resin of a different type from the (meth)acrylic resin contained in the (meth)acrylic resin composition.
5. The optical film according to claim 1, wherein The first resin composition and the second resin composition include a polycarbonate resin. 6 . A polarizing plate protective film, comprising the optical film according to claim 1 . 7 . A polarizing plate comprising the polarizer protective film according to claim 6 . 8 . An image display device comprising the polarizing plate according to claim 7 .
Citation Information
Patent Citations
Thermoplastic resin film and method of manufacturing thermoplastic resin film
JP2010125688A